Study of anti-cancer mechanism: Neolamarckia cadamba leaves exposed with electric field on HeLa cell - Mohamad Ishak, Daing Noor Farhanah; Abdul Jamil, Muhammad Mahadi; Adon, Mohamad Nazib; Ma'radzi, Ahmad Alabqari; Abdul Wahab, Ridhwan (Institute of Electrical and Electronics Engineers Inc., 2018)
-Electroporation occurs when the electric field is applied and cause the permeabilization of the HeLa cell membrane. It has two type that is reversible electroporation and irreversible electroporation. In this study, it suggests that reversible electroporation may become an important technique in treating cancer. In this study cervical cancer cell (HeLa cell) will be used as a sample for electroporation process. After electroporation process completed, compound extract (Neolamarckia Cadamba Leaves) will be used as anti-cancer within the culture media. This study will demonstrate a new method for cancer treatment via combination of natural compound plus the electric field. The treatment aims to investigate and evaluate the electroporation and compound extract test effect on HeLa cell. By combining this two technique electroporation and absorption of the compound extract on HeLa cell potentially might be a new technique for anti-cancer process treatment.